Pharmaceutical forms in Antidotarium Nicolai - Marta Pocuca; Dragan Stupar (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2006)
Pharmaceutical forms are equally important as pharmacodynamic effect of drug for expression of therapeutic effect. Antidotarium Nicolai was the first pharmacopoeia written in the beginning of the 12th century by Nicolaus Salernitanus. Pharmaceutical forms were not described clearly in terms of type, structure, technological process and application. Salerno's pharmacotherapy, as it can be seen from the Antidotarium, was based on "sugar-honey pharmacy" and the only difference between pharmaceutical forms was viscosity of forms. The following forms are described in the Antidotarium: electuaria, morsuli, pillules, trochisci, sirupi, emplastra, unguenta and olea. Antidotarium Nicolai is of unique importance since it is the first attempt of systematisation of pharmaceutical forms. Although today's criteria differ significantly from Nicolaus's, this book still has a great value as it represents the basis for all further pharmacopoeias written many years after Antidotarium Nicolai.